About the «Guide to the halls of the Vernadsky State Geological Museum of RAS» - V. N. Коmaгоv (Известия высших учебных заведений: Геология и разведка)
The guidebook to the Vernadsky State Geological Museum RAS provides the detailed information about the features of the structure and history of the Earth's geospheres, geological activity of living matter and the man. It tells about the riches of the Earth's bowels of Russia, the geological structure of the surroundings of Moscow, the collections of the Museum and its history.